2019
DOI: 10.1038/s41598-019-44410-0
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic reasoning for colossal N supersaturation in austenitic and ferritic stainless steels during low-temperature nitridation

Abstract: Colossal N supersaturation of ferritic as well as austenitic stainless steels during low temperature gaseous nitridation treatments has lately gained much technological significance. However, available thermodynamic models to calculate the N paraequilibrium solubility limits have failed to explain the levels of colossal N supersaturation observed in several cases of nitrided ferritic/austenitic stainless steels. In this work, we show that consideration of N dissolution induced spinodal decomposition is essenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Preferential bonding of N to Cr atoms has been observed (see Section 4.3). On the basis of the observation of these short-range ordered Fe-Cr-N clusters Sasidhar and Meka [150] hypothesized that the "colossal" supersaturation implies a spinodal decomposition, which produces the nano-sized precipitates.…”
Section: Microstructure and Phase Composition Of The Modified Layersmentioning
confidence: 99%
“…Preferential bonding of N to Cr atoms has been observed (see Section 4.3). On the basis of the observation of these short-range ordered Fe-Cr-N clusters Sasidhar and Meka [150] hypothesized that the "colossal" supersaturation implies a spinodal decomposition, which produces the nano-sized precipitates.…”
Section: Microstructure and Phase Composition Of The Modified Layersmentioning
confidence: 99%
“…In addition, the nitriding at high temperature can also cause an α to y transition in the surface microstructure depending on the incorporation of nitrogen in the process [24]. The colossal interstitial nitrogen supersaturation in the ferrite (α) phase, similar to that observed for the γ N phase, was also predicted by theoretical works and identified in nitriding works in duplex steels that indicate that both phases are formed by means of a spinodal-like decomposition of ferrite into Cr-rich and Fe-rich ferrite phases [7,25,26]. However, in those experimental works that feature this mechanism, the matrix remains with its BCC crystal structure, and nitrides are formed.…”
Section: Introductionmentioning
confidence: 53%
“…Atom probe tomography (APT) observations seem to support this hypothesis [202]. On the basis of these studies it was suggested that the "colossal supersaturation" implies a spinodal decomposition, which produces the nano-sized precipitates [203]. In Fe-Cr-Ni alloys with a Cr content higher than 12 wt.%, nitrided at 380 • C for 3 h, the outer N-rich zone consisted of γ'-Fe 4 N-like long-range order (LRO) regions and Cr-N short-range order (SRO) regions, which were indicated as γ N ', while the inner zone was an interstitially disordered expanded austenite with SRO regions of Cr and N atoms [204].…”
Section: Expanded Austenite: Is It Really a Solid Solution?mentioning
confidence: 99%